Filtering Data of High-Resolution Terrestrial Laser Scanner and Effects of Filtrations on the Landslide Monitoring - Mustafa Zeybek; İsmail Şanlıoğlu; Aşır Genç (Doğal Afetler ve Çevre Dergisi)
Monitoring and investigating natural disasters is one of the most important works for decreasing damages and preventing losses. In this study, using Terrestrial Laser Scanning (TLS) techniques for landslide monitoring studies, processing data obtained from these techniques and evaluating the results were performed. Research was carried out on a landslide zone which occurred in the Middle Taurus Mountains. When previous studies were examined, deformations reaching up to 5m were formed in the region. In this article, automatic filtering of terrestrial laser scanning data, filtering of trees and other objects on the earth and acquiring digital elevation model (DEM) and by means of this model, assessing changes occurring in the elevation components on the land surface and the effect of filtering algorithms on analysis were investigated. Progressive Morphological Filtering (PMF) algorithm was used for this research. Point cloud filtering algorithm has automatically obtained two filtered data as the ground and the non-ground. Using the real surface ground models of the earth to obtain DEM model’s reflection of real earth surface has a direct impact on determining the true surface deformation. In conclusion, things such as trees, objects, vehicles, houses, man-made structures and vegetation must be filtered out of data because analysis in a regional base may cause misinterpretation without filtered point cloud data. The results revealed that the filtered comparison analyzes were evaluated easier. In addition, changes in plant cover in different periods for the comparison of models has been automatically filtered and the landslide movements have been interpreted with purifying from artificial distortion.